Literasi AI Bagi Mahasiswa Indonesia dan Menyelaraskan Pembelajaran dengan Model Eropa - Elisabet Simanjuntak; Piladelpia Trifosa Ginting; Raisha Mei Nabel Pakpahan; Muhammad Joharis Lubis (Lembaga Pengembangan Kinerja Dosen, 2025)
Artificial Intelligence (AI) in learning can serve as a tool for students to acquire knowledge. However, the understanding and use of AI in education still face various challenges. Some universities have started integrating AI learning into their curricula, but its implementation remains limited and uneven across different institutions. Additionally, the level of AI literacy among students in Indonesia is still relatively low. Adequate AI literacy is crucial for students to optimize the use of this technology without excessive dependence and to understand its ethical implications.This research aims to assess students' understanding of AI literacy and explore how AI literacy education can be integrated with the European model. A mixed-method approach is used in this study, combining quantitative research through questionnaires and qualitative research through interviews. The results indicate that students in Indonesia have a fairly good understanding of AI literacy. However, several challenges remain, including students' dependence on AI and ethical issues related to its use.Therefore, collaboration among various stakeholders, including universities, the government, and industry, is essential to enhance students' AI literacy skills. Efforts can include training programs, providing access to AI resources, and adopting AI-based learning models that have been implemented in Europe. Through these measures, it is expected that students' AI literacy will improve, supporting the advancement of technology-based education in Indonesia.